Construction of a psychometric questionnaire of aggressiveness for adolescents from 12 to 17 years old - Córdova Pomachagua, Rosario Cielo (2026)
Aggression is a heightened emotional state during adolescence; however, there are few instruments available to measure it in the Peruvian context. Therefore, the objective of this study was to construct and validate a psychometric test to assess aggression in adolescents. The questionnaire was administered to 115 students aged 12 to 17 years. The results showed an Aiken's V value of 0.91, Pearson's correlation coefficients greater than 0.20 for the items, confirmatory factor analysis yielded values of 0.30 and 0.68, and a Cronbach's alpha value of 0.869. It is concluded that the questionnaire has adequate content validity and internal consistency for measuring aggression in adolescents aged 12 to 17 years.